Importance of anatomical site in the metastases of auricular cutaneous squamous cell carcinoma: an observational study. Issue 7 (September 2020) - Sayan, A.; Paraneetharan, S.; Ilankovan, V.
Abstract: Malignancies of the auricular skin tend to metastasise to preauricular, parotid, facial, and level II (possibly to levels IV and V) lymph nodes in an unpredictable manner. Over the years, we have observed that this pattern of metastasis is commonly linked to lesions that involve the lower half of the ear. To find conclusive evidence based on this hypothetical observation, we retrospectively studied 108 patients who presented with squamous cell carcinoma (SCC) of the ear, and looked at the exact auricular site of the lesion at presentation, incidence of metastasis, nodal involvement, treatment, and survival outcome. The literature was reviewed extensively to ensure detailed presentation of the lymphatic drainage pathway. The pattern of spread and outcome were evaluated. This study has shown that there is a significant correlation between anatomical position and risk of metastasis, and that lesions of the lower half of the ear are more prone to metastasis. These patients therefore may warrant early imaging, possible sentinel node biopsy, or even selective neck dissection with simultaneous primary excision.